New Trends in Engineering Research 2024 International Conference of Experimental and Numerical Investigations and New Technologies, CNNTech 2024 - Mitrovic, Nenad; Mladenovic, Goran; Mitrovic, Aleksandra (Lecture Notes in Networks and Systems, 2024)
XI, 394 p.